Automatic Generation of Validated Specific Epitope Sets - Sebastian Carrasco Pro; John Sidney; Sinu Paul; Cecilia Lindestam Arlehamn; Daniela Weiskopf; Bjoern Peters; Alessandro Sette (Journal of Immunology Research)
Accurate measurement of B and T cell responses is a valuable tool to study autoimmunity, allergies, immunity to pathogens, and host-pathogen interactions and assist in the design and evaluation of T cell vaccines and immunotherapies. In this context, it is desirable to elucidate a method to select validated reference sets of epitopes to allow detection of T and B cells. However, the ever-growing information contained in the Immune Epitope Database (IEDB) and the differences in quality and subjects studied between epitope assays make this task complicated. In this study, we develop a novel method to automatically select reference epitope sets according to a categorization system employed by the IEDB. From the sets generated, three epitope sets (EBV, mycobacteria and dengue) were experimentally validated by detection of T cell reactivity ex vivo from human donors. Furthermore, a web application that will potentially be implemented in the IEDB was created to allow users the capacity to generate customized epitope sets.